A case of tularemia in the Republic of Crimea - M. I. Grusha; S. B. Hudoyarov; A. A. Arzhanovskaya; D. R. Kosorotov; R. V. Zonova (Журнал инфектологии, 2024)
Tularemia is a bacterial disease of humans; wild and domestic animals. The causative agent of tularemia is Francisella tularensis; which is a gram-negative bacterium in the form of a coccobacillus. This disease has multiple clinical manifestations depending on the path of infection; the virulence of the infecting bacterial strain and the underlying health status of infected individuals. Systemic infections (for example; pulmonary and typhoid forms) and complications are rare; but can be life-threatening. Most people suffer from a local infection (for example; skin ulcers; conjunctivitis or pharyngitis) with regional lymphadenopathy; which develops to suppuration in about 30% of patients and a chronic course of infection. The disease is spread through vectors such as mosquitoes; horseflies; deer flies and ticks. People can become infected with this disease through direct contact with sick animals; eating infected animals; drinking or direct contact with contaminated water and inhaling aerosols containing bacteria. There are natural foci of tularemia on the territory of the Republic of Crimea; which; combined with low awareness of the population; creates prerequisites for the formation of an unfavorable epidemic situation on the peninsula. The purpose of this study is to study the features of the clinical course of tularemia. A retrospective analysis of the patient’s medical history with the final diagnosis was carried out: tularemia; glandular form; moderate severity. The following keywords were used to search for literary sources: “tularemia”; “natural foci of tularemia in the Crimea”. The eLibrary search engine was used to search for literature.ru — scientific electronic library”; the PubMed search engine was used to search for English-language literature.